Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3389/fonc.2016.00126
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Diffusion-Weighted Imaging in the Characterization of Malignant, Benign, and Healthy Breast Tissues and Molecular Subtypes of Breast Cancer

Abstract: The role of apparent diffusion coefficient (ADC) in the diagnosis of breast cancer and its association with molecular biomarkers was investigated in 259 patients with breast cancer, 67 with benign pathology, and 54 healthy volunteers using diffusion-weighted imaging (DWI) at 1.5 T. In 59 breast cancer patients, dynamic contrast-enhanced MRI (DCEMRI) was also acquired. Mean ADC of malignant lesions was significantly lower (1.02 ± 0.17 × 10−3 mm2/s) compared to benign (1.57 ± 0.26 × 10−3 mm2/s) and healthy (1.78… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
40
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 67 publications
(113 reference statements)
7
40
1
Order By: Relevance
“…[24,25] However, prior studies [8,22] have found that TNBC has a higher mean ADC value than other breast cancer subtypes due to TNBC's necrotic components. Our results confirmed findings of higher mean ADC value (P<0.001) in TNBC in a univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[24,25] However, prior studies [8,22] have found that TNBC has a higher mean ADC value than other breast cancer subtypes due to TNBC's necrotic components. Our results confirmed findings of higher mean ADC value (P<0.001) in TNBC in a univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ADC has been utilized as an indicator of tumour aggressiveness, Ki‐67 expression, tumour cellularity and the expression of prognosis biomarkers in breast cancer . Recent studies have reported a correlation between ADC and the molecular markers of breast cancer . In addition to direct analysis of the entire tumour, DWI information on the breast tumour–stromal boundary and adjacent tissue surrounding the tumour has also been combined to associate DWI parameters with pathological factors or to predict responses to treatment …”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23] Recent studies have reported a correlation between ADC and the molecular markers of breast cancer. [24][25][26][27] In addition to direct analysis of the entire tumour, DWI information on the breast tumour-stromal boundary and adjacent tissue surrounding the tumour has also been combined to associate DWI parameters with pathological factors or to predict responses to treatment. 28,29 In this study, we hypothesized that the ADC values of the tumour and surrounding peritumoral stroma may be distinct and may reflect the heterogeneity of the tumour microenvironment in breast cancer.…”
mentioning
confidence: 99%
“…Moreover, during the progression of disease as in LABC, necrosis is commonly seen, and Sharma et al have reported that ADC is a reliable indicator to monitor these islets of necrotic regions (Figure ). Patients with early breast cancer had significantly lower ADC compared with those with LABC, and no association was found between ADC and menopausal status . These results thus provide information on tumor biology and microstructural features.…”
Section: Mri‐related Methods In the Study Of Breast Cancer Metabolismmentioning
confidence: 70%